ISLAMIC EDUCATION CURRICULUM PLANNING MODEL - Intan Sari, Arrum; Setyaningsih, Rini (Al Ulya: Jurnal Pendidikan Islam, 2023)
The purpose of this research is to find out how the Islamic education curriculum planning model takes into account 1) epistemology, 2) ideology, and 3) the Islamic education curriculum planning model in Tyler's view which is associated with the opinions and theories of Zainal Arifin. The method used in this study is Library Research which is carried out by collecting data in the form of text in online/offline libraries, E-Books, and journals using inductive analysis techniques. The main literary sources used are two books (Zainal Arifin and Oemar Hamalik) and one article (Mukh Nursikin). The approach used in this study is to 1) record all data findings in the form of text obtained from the literature, 2) combine the data obtained, 3) researchers analyze the data obtained, and 4) criticize the results obtained. The results of this study are that the interactive rational curriculum planning model that adapts to thoughts and situations is very suitable to be applied and this model pays attention to curriculum development after planning. Supported by the theory of the curriculum model, namely the ideology and epistemology of the Islamic education curriculum, namely knowledge, methods, structure, and basis which are used as guidelines.